The Analysis of EFL Students` Ability in Translating Text from Indonesian Into English at Lampung State Islamic University - kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2020)
The objectives of this research are to know the ability of UIN Raden Intan English department to translate text from Indonesian to English and to know errors made by students in translating. The methodology employed was quantitative content analysis with a research instrument is a rubric. Results show students translation abilities of UIN Raden Intan English Department are very good with 9 students (33.4 %), fair with 8 students (29.6 %), good with 5 students (18.5 %), bad (14.5 %), and almost excellent 1 student(3.7%). Translation errors are grammatical errors,  missing word, mother tongue word use, different meaning production, word order, word choice, and misspelling.